2017
DOI: 10.1038/ncomms14607
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ is required for cytotoxic T cell-dependent cancer genome immunoediting

Abstract: Genetic evolution that occurs during cancer progression enables tumour heterogeneity, thereby fostering tumour adaptation, therapeutic resistance and metastatic potential. Immune responses are known to select (immunoedit) tumour cells displaying immunoevasive properties. Here we address the role of IFN-γ in mediating the immunoediting process. We observe that, in several mouse tumour models such as HA-expressing 4T1 mammary carcinoma cells, OVA-expressing EG7 lymphoma cells and CMS5 MCA-induced fibrosarcoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
82
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 66 publications
(99 reference statements)
3
82
1
1
Order By: Relevance
“…15 It was recently reported that that interferon (IFN) released by tumourinfiltrating lymphocytes can induce DNA damage and mutations, promoting the MHC/HLA class I heterogeneity observed in primary tumours. 16 These data suggest that tumour-infiltrating lymphocytes per se may possibly promote the Generation of Diversity in the primary tumour and that the genetic instability observed in some tumours may not be the main driving force inducing MHC/HLA changes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…15 It was recently reported that that interferon (IFN) released by tumourinfiltrating lymphocytes can induce DNA damage and mutations, promoting the MHC/HLA class I heterogeneity observed in primary tumours. 16 These data suggest that tumour-infiltrating lymphocytes per se may possibly promote the Generation of Diversity in the primary tumour and that the genetic instability observed in some tumours may not be the main driving force inducing MHC/HLA changes.…”
Section: Introductionmentioning
confidence: 93%
“…We have defined two different stages of this process: a ‘permissive phase’, when T lymphocytes are infiltrating the tumour niche and killing cancer cells; and an ‘encapsulated phase’, when the tumour is composed solely of MHC class I‐negative cells and T lymphocytes are retained only in the surrounding stroma of a granuloma‐like structure . It was recently reported that that interferon (IFN) released by tumour‐infiltrating lymphocytes can induce DNA damage and mutations, promoting the MHC/HLA class I heterogeneity observed in primary tumours . These data suggest that tumour‐infiltrating lymphocytes per se may possibly promote the Generation of Diversity in the primary tumour and that the genetic instability observed in some tumours may not be the main driving force inducing MHC/HLA changes.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, they produce TNF-related apoptosis-inducing ligand (TRAIL) to engage with TRAIL receptors on tumor cells and in turn induce tumor cell apoptosis [3]. Finally, activated lymphocytes produce IFN- γ , which is a pleiotropic cytokine with a wide range of activity; IFN- γ simultaneously induces apoptosis, tumor dormancy, and immunoediting in tumor cells that could lead to tumor relapse and progression [48]. Paradoxically, chronic exposure of cells to IFN- γ facilitates the development of hepatocellular carcinoma [9], colorectal carcinoma [10], and papilloma [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to apoptosis inducing and tumor inhibitory functions, IFN- γ can also induce aberrant DNA methylation [29, 30] or genetic alteration in tumor cells [4], resulting in tumor progression and relapse. IFN- γ -induced tumor immunoediting is mediated through several mechanisms which include the induction of tumor antigen loss [3034], upregulation of PD-L1 in tumor cells [35], recruitment of myeloid-derived suppressor cells (MDSCs) and tumor associated macrophages (TAMs) to the tumor site [36, 37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation